Effect of surface pretreatments on the deposition of polycrystalline diamond on silicon nitride substrates using hot filament chemical vapor deposition method - Dayangku Noorfazidah, Awang Sh'ri (2009)
The deposition of diamond films on a silicon nitride (Si3N4) substrate is an attractive technique for industrial applications because of the excellent properties of diamond.Diamond possesses remarkable physical and mechanical properties such as chemical resistant,extreme hardness and highly wears resistant.Pretreatment of substrate is very important prior to diamond deposition to promote nucleation and adhesion between coating and substrate. Polycrystalline diamonds films have been deposited on silicon nitride substrate by Hot Filament Chemical Vapor Deposition (HF-CVD)method.The Si 3N4 substrates have been subjected to various pretreatment methods prior to diamond deposition namely chemical etching and mechanical abrasion.The structure and morphology of diamond coating have been studied using X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) while diamond film quality has been characterized using Raman spectroscopy.The adhesion of diamond films has been determined qualitatively by using Vickers hardness tester.It was found that the diamond films formed on chemical pretreated substrates has cauliflower morphology and low adhesive strength but also have low surface roughness.Substrates that pretreated with sand blasting have yield diamond film with well-facetted morphology with high crystallinity and better adhesion. However,the surface roughness of the diamond film deposited on substrates pretreated with blasting are also higher.